Rheological effects on gas dispersion in a pilot scale mechanical flotation cell - Shabalala, Ntokozo Zinhle Precious (Centre for Minerals Research, 2016)
Froth flotation is a separation method used for the beneficiation of a considerable portion of the world's mineral ores. The majority of flotation occurs in mechanical flotation cells, where effective gas dispersion is a primary requirement for particle-bubble contacting. Due to the mineralogical complexity of ores, it is required that particles be ground even finer to liberate valuable minerals. Mining operations tend to run flotation circuits at fairly high solids concentrations in order to maximise residence time, accommodate higher tonnages and limit water consumption. Mineral slurries processed at fine particle sizes and high solids concentrations have been shown to exhibit non-Newtonian rheological behaviour. The effect of slurry rheology on gas dispersion in a 100 litre mechanical flotation cell was investigated by varying the solids concentration. The study was conducted using kaolin, Bindura nickel and Platreef slurries. All three ores displayed typical non- Newtonian rheological behaviour where the slurry yield stress and viscosity increased exponentially with solids concentration. Bubble size varied from 0.55 to 1.10 mm for all the ores tested. At low solids concentration bubble size was found to decrease with impeller speed, a characteristic trend that was expected. At moderate solids concentrations bubble size was found to either increase/remain relatively constant with impeller speed; this trend was also expected. Unexpectedly, at the highest solids concentration, a dramatic decrease in bubble size was observed. This unexpected drop in bubble size was attributed to slurry rheology. It was also observed that there was a slight increase in bubble size at the highest solids concentration with increasing impeller speed. This increase was attributed to a trade-off relationship between the rheology of the slurries and the existing hydrodynamics (as a result of the rotating impeller). Gas hold-up varied from 2 to 15% across all the ores tested. At low solids concentrations gas hold-up increased with impeller speed as expected. At moderate solids concentration gas hold-up was viewed to either increase/remain relatively constant with impeller speed. A significant drop in gas hold-up was observed at the highest solids concentration. The gas hold-up however still increased with impeller speed albeit at a lower rate at the highest solids concentrations. This drop in gas hold- up at the highest solids concentration (along with the decrease in bubble size) was attributed to the effect of slurry rheology. At high solids concentrations, all three slurries (kaolin, Bindura nickel and Platreef) exhibit non-Newtonian behaviour illustrated by means of high viscosities and yield stresses. High viscosities result in turbulence damping in the cell which inhibits bubble break-up, resulting in larger bubbles and correspondingly lower gas hold-up. It was concluded in this study that the yield stress is the dominant rheological property due to the significant changes observed with increasing solids concentration. High yield stresses resulted in the formation of a 'cavern' of slurry around the impeller region. Within this 'cavern', high power intensities exist around the impeller where small bubbles are formed. However due to the formation of the 'cavern', the slurry in the bulk cell remains relatively stagnant. As a result small bubbles formed around the impeller remain localised in the 'cavern' and cannot be dispersed throughout the cell. This localization and poor dispersion of bubbles resulted in low gas hold-ups.